Quality Management of Maternal and Child Health Services in Antenatal Care Services in The Time of The Covid-19 Pandemic - Sinaga, Siti Nurmawan (Universitas Aisyah Pringsewu, 2022)
This study aims to analyze the Quality Management of Maternal and Child Health Services in Antenatal Care Services during the Covid-19 Pandemic at the Ketapang Nusantara Health Center, Central Aceh Regency in 2022. This type of research uses quantitative research using a Cross Sectional Description approach. in this study used an extensive dataset to see many cases and the relationship between variables. The results of this study are that the satisfaction level of Satisfied is 47 people (54.0%), and the Minority has a Satisfaction level of Less Satisfied as many as 1 person (1.1%). The results of statistical tests using the chi-square test obtained a p-value of 0.006 less than 0.05, meaning that there is a significant relationship between the Product/Service Outcome Relationship, in Quality Management of Maternal and Child Health Services in Antenatal Care Services during the Covid-19 Pandemic Period in Indonesia. Ketapang Nusantara Health Center, Central Aceh Regency in 2022.Abstrak: Penelitian ini bertujuan untuk menganalisa Manajemen Kualitas Pelayanan Kesehatan Ibu Dan Anak Pada Pelayanan Antenatal Care Di Masa Pandemi Covid-19 Di Puskesmas Ketapang Nusantara Kabupaten Aceh Tengah Tahun 2022. Jenis penelitian ini menggunakan penelitian kuantitatif dengan menggunakan pendekatan Diskripsi Cross Sectional. pada penelitian inni menggunakan dataset yang ekstensif untuk melihat banyak kasus dan hubungan antar variable. Hasil penelitian ini yaitu memiliki tingkat kepuasaan Puas sebanyak 47 orang (54,0%) ,dan Minoritas memiliki tingkat kepuasaan Kurang Puas sebanyak 1 orang (1,1 %). Hasil uji statistik dengan menggunakan uji chi-square diperoleh p-value sebesar 0,006 kurang dari 0,05 artinya ada hubungan yang signifikan antara Hubungan Produk/Hasil Layanan, dalam Manajemen Kualitas Pelayanan Kesehatan Ibu Dan Anak Pada Pelayanan Antenatal Care Di Masa Pandemi Covid-19 Di Puskesmas Ketapang Nusantara Kabupaten Aceh Tengah Tahun 2022